Attitudes, biology or environment: sexualised behaviour in the workplace - Brooks, Jordan (2024)
Workplace Sexual Harassment (WSH) research predominantly focuses on the effect that sexual harassment has on (female) victims or the organisation, with little being understood about the key characteristics or underlying motivations of those who display WSH. This has implications for our understanding of WSH and identifying appropriate interventions. This thesis aimed to investigate the key characteristics and motivations for displaying WSH, examining the impact of environmental, personality, and/or societal factors for displaying such behaviour.